ANALISIS PERBAIKAN WORK STATION PADA PROSES PRODUKSI GARMENT DENGAN MENGGUNAKAN PENDEKATAN ANTHROPOMETRI - Mentari Rasyid; Surachman Surachman; Sugiono Sugiono (Journal of Engineering and Management in Industrial System, 2016)
ABSTRACT  Productivity garment greatly influenced by the work station facilities and presence in the workplace . UD Aliya -  Malang is one example as an object of research . Based on the research conducted , there are still some problems . This is also supported by the operator of complaints about the draft working facilities , the work table is often used as a medium to carry out the activity of cutting material (cloth or canvas). Incompatibility between the dimension table with the body dimensions of operators resulted in operators often complain , and perform movements beyond the normal limits . By using anthropometric approach , the results obtained is the size of the table corresponding to the dimensions of the body of the operator , namely the size of the table is 117cm x 69cm x 98,41cm . Keywords: Work Station, Facilities of Work, Anthropometry